2007
DOI: 10.1111/j.1468-3083.2006.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis vulgaris and human leukocyte antigens

Abstract: Different antigens and alleles from both HLA classes I and II were seen in a significantly higher frequency in patients with psoriasis vulgaris. HLA Cw*0602 and DRB1*0701 were represented in different reports, and the former was related mainly to psoriasis type I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
2
19
0
2
Order By: Relevance
“…27 Psoriasis has been reported to be associated with HLA-B*13, -B*27, -B*37, -B*39, -B*46 and particularly B*57. 15,16 The present study suggests that B*57 is the only B locus allele associated with psoriasis, which is consistent with other studies. 15,16 Cassia et al (2007) showed that in a mixed population, the allele B*57 was significantly more frequent in psoriatic patients.…”
Section: Discussionsupporting
confidence: 94%
“…27 Psoriasis has been reported to be associated with HLA-B*13, -B*27, -B*37, -B*39, -B*46 and particularly B*57. 15,16 The present study suggests that B*57 is the only B locus allele associated with psoriasis, which is consistent with other studies. 15,16 Cassia et al (2007) showed that in a mixed population, the allele B*57 was significantly more frequent in psoriatic patients.…”
Section: Discussionsupporting
confidence: 94%
“…From our experience on 95 patients, the total distribution of the HLA class II polymorphisms, known to be peculiar to coeliac disease, IDDM, psoriasis, vitiligo, autoimmune thyroiditis, Crohn's disease, rheumatoid arthritis [20][21][22][23] was not significantly different from the controls. What is strikingly different is that Turner patients evolve towards autoimmunity much more frequently than people with normal karyotype without any relevant excess of the putative immunogenetic risk markers.…”
Section: The Unusual Immunogenetic Phenotype Of Turner Syndromementioning
confidence: 52%
“…Increasing evidences indicate that psoriasis is also a genetic disease triggered by multiple environmental factors, such as smoking, chronic infections, stress, climate changes. Many studies about the association between human leukocyte antigens (HLA) and psoriasis have been reported for a long time [2, 3]. In recent studies, much attention have been paid on the role of epigenetic changes (e.g.…”
Section: Introductionmentioning
confidence: 99%